2011
DOI: 10.1136/thx.2010.151621
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific trends in lung cancer incidence and survival: a population study of 40 118 cases

Abstract: Background and aim Lung cancer is increasingly affecting women. The aim of this study was to identify sex-specific trends in lung cancer incidence and survival. Methods Complete national data on 40 118 cases from the Cancer Registry of Norway sampled from 1988 to 2007 are presented, with incidence rates, 1-and 5-year relative survival in 5 year intervals and multivariate HRs adjusted for covariates, each with 95% CIs. Results Lung cancer incidence increased by 64%, with an age-adjusted annual average increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
104
4
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(130 citation statements)
references
References 37 publications
14
104
4
8
Order By: Relevance
“…Several studies have indicated better survival in females with NSCLC than males [4,65,66]. Explanations to this difference has been thought to result from diverging clinicophatological characteristics and altered susceptibility to environmental exposures between men and women.…”
Section: Discussion Of Main Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have indicated better survival in females with NSCLC than males [4,65,66]. Explanations to this difference has been thought to result from diverging clinicophatological characteristics and altered susceptibility to environmental exposures between men and women.…”
Section: Discussion Of Main Resultsmentioning
confidence: 99%
“…Norwegian studies have suggested females to have better prognosis than males following lung cancer treatment [4,78]. A retrospective study from Haukeland University Hospital in Bergen (Norway) in which the analysis were based on 351 patients (32% females), relative 5-years survival in patients operated for non-small cell lung cancer was 66.1% for females and 45.7% for males.…”
Section: Discussion Of Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anti-smoking campaigns are strongly promoted in Thailand; however, fewer females than males seem to be responding (Sagerup et al, 2011) and the numbers of new lung cancer cases in females is still gradually rising. In the last 10 years, the number of breast cancer cases in females has noticeably increased.…”
Section: Discussionmentioning
confidence: 99%